2020
DOI: 10.1186/s12881-020-0987-4
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 rs2231142 variant in hyperuricemia is modified by SLC2A9 and SLC22A12 polymorphisms and cardiovascular risk factors in an elderly community-dwelling population

Abstract: Background: The ABCG2 rs2231142 single nucleotide polymorphism (SNP) is one of the most significant genetic variants associated with hyperuricemia (HUA) in Asian populations. However, the risk of ABCG2 rs2231142 variants for HUA could interact with other important HUA risk variants and cardiovascular factors. This study investigated the effects of the combined association among ABCG2 rs2231142 and multiple HUA genetic variants or cardiovascular risk factors on HUA risk and serum uric acid (sUA) levels in an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
4
12
2
Order By: Relevance
“…We found that the minor allele frequency was 0.37 for the C allele, contrary to what was reported in a Chinese population, where the C allele had a higher frequency, in addition to its being associated with hypertension (Wu et al, 2015). However, the link between the XDH (rs1042039) polymorphism and hypertension was not demostrated in Taiwanese women (Lee et al, 2019). In the present study, we did not find a statistically significant different distribution of the C allele between the hyperuricemic and normouricemic groups, and the risk allele was also not associated with any component of the metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…We found that the minor allele frequency was 0.37 for the C allele, contrary to what was reported in a Chinese population, where the C allele had a higher frequency, in addition to its being associated with hypertension (Wu et al, 2015). However, the link between the XDH (rs1042039) polymorphism and hypertension was not demostrated in Taiwanese women (Lee et al, 2019). In the present study, we did not find a statistically significant different distribution of the C allele between the hyperuricemic and normouricemic groups, and the risk allele was also not associated with any component of the metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 83%
“…between serum uric acid levels and the traits of metabolic syndrome has been previously analyzed (Lin et al, 2006;Zhang et al, 2020a), although some authors found no causal evidence of uric acid levels being associated with metabolic syndrome and its components (Wang et al, 2020). According to our results, being a man, being overweight or obese, or having dyslipidemia are related to high uric acid levels (Figure 1).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In a genome-wide association study, additive genetic risk score of nonsynonymous variants of ABCG2 (rs2231142) and SLC2A9 (rs16890979) showed graded associations with uric acid and gout 56 . It was also recently reported that the association of ABCG2 rs2231142 with hyperuricemia is modified by SLC2A9 polymorphism in an elderly Chinese population 57 . Although the causative mechanism for the synergistic effects of polymorphisms in platinum intake and export pathways, such as SLC31A1 and ABCG2 , is still largely unknown, the association of their interaction with clinical outcomes suggests the combined relevant genotypes of SLC31A1 and ABCG2 as potential pertinent and actionable pharmacogenetic biomarkers for platinum-based chemotherapy of NSCLC, especially for some demographically stratified subgroups patients.…”
Section: Discussionmentioning
confidence: 83%